2018
DOI: 10.2147/cia.s151211
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic ability of cystatin C and homocysteine plasma levels for long-term outcomes in very old acute myocardial infarction patients

Abstract: Background and aimsThis study sought to evaluate the prognostic powers of combined use of cystatin C (Cys C) and homocysteine (Hcy) at predicting adverse events of patients >80 years old with acute myocardial infarction (AMI).Patients and methodsThe analysis involved 753 patients >80 years old undergoing coronary angiography for chest pain in China from January 2006 to December 2012. Kaplan–Meier method was used for survival and major adverse cardiac events (MACE) rates. Multivariate Cox regression was perform… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 35 publications
0
7
0
Order By: Relevance
“…CSTB is a member of the cystatin superfamily that encodes the Cystatin B protein that functions as protease inhibitor. It has been shown that Cystatin C, another member of cystatin superfamily, is a determinant of serum levels of Hcyst 14 , 15 . We also identified a novel locus associated with two related coagulation traits (PT and INR) on chromosome 13 situated near LINC01070 , a gene that encodes a long noncoding RNA.…”
Section: Resultsmentioning
confidence: 99%
“…CSTB is a member of the cystatin superfamily that encodes the Cystatin B protein that functions as protease inhibitor. It has been shown that Cystatin C, another member of cystatin superfamily, is a determinant of serum levels of Hcyst 14 , 15 . We also identified a novel locus associated with two related coagulation traits (PT and INR) on chromosome 13 situated near LINC01070 , a gene that encodes a long noncoding RNA.…”
Section: Resultsmentioning
confidence: 99%
“…Cys C is a strong independent predictor of long-term all-cause death and major adverse cardiac events in elderly patients with acute myocardial infarction. The combined detection of Cys C and HCY further improves the predictive value [ 25 ]. Cys C can inhibit HCY decomposition, increase its concentration in blood, and interact with factors including plasma HCY and histones, thereby increasing the risk of hypertension and gestational diabetes in pregnant women and further increasing the risk of premature birth, miscarriage, and fetal intrauterine growth restriction [ 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…The above results suggest that insulin combined with metformin can effectively reduce the serum Cys C and Hcy levels of patients, thus improving the patient's condition. Previous findings have indicated that the therapeutic effect and complications of patients with GDM could be predicted by monitoring factors in serum of patients with GDM (24).…”
Section: Discussionmentioning
confidence: 99%